2007
DOI: 10.1063/1.2423011
|View full text |Cite
|
Sign up to set email alerts
|

Electronic characteristics of fluorene/TiO2 molecular heterojunctions

Abstract: The electronic properties of molecular junctions of the general type carbon/molecule/TiO2Au were examined as examples of "molecular heterojunctions" consisting of a molecular monolayer and a semiconducting oxide. Junctions containing fluorene bonded to pyrolyzed photoresist film (PPF) were compared to those containing Al2O3 instead of fluorene, and those with only the TiO2 layer. The responses to voltage sweep and pulse stimulation were strongly dependent on junction composition and temperature. A transient cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
77
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(88 citation statements)
references
References 61 publications
10
77
1
Order By: Relevance
“…It has been suggested that these spikes are capacitance; however the timescale is too long. The spikes have been reported by other groups in their memristors (see for example, [14]), however they are usually overlooked or attributed to artefacts arising from the experimental set-up or not reported at all (many researchers only report the I − V curves to demonstrate that they have a memristor). However, the current spike is an equilibrating process that is responsible for the frequency dependence of the I − V curves.…”
Section: Properties Of Memristor Spikesmentioning
confidence: 94%
“…It has been suggested that these spikes are capacitance; however the timescale is too long. The spikes have been reported by other groups in their memristors (see for example, [14]), however they are usually overlooked or attributed to artefacts arising from the experimental set-up or not reported at all (many researchers only report the I − V curves to demonstrate that they have a memristor). However, the current spike is an equilibrating process that is responsible for the frequency dependence of the I − V curves.…”
Section: Properties Of Memristor Spikesmentioning
confidence: 94%
“…Some techniques for achieving sub-nanometer substrate flatness include the Au deposition on a thiol primer on silicon [120] and the pyrolysis of photoresist in a reducing atmosphere, resulting in a substrate dubbed ''pyrolyzed photoresist film,'' or PPF. [121,122] Both substrate flatness and defect occurrence favor the use of small junction areas where possible. [59,60,63,66] Making a second, or top, contact between a conductor (usually metallic) and a molecular monolayer over an area covering at least thousands of molecules has proven challenging.…”
Section: Progress With Ensemble Molecular Junctionsmentioning
confidence: 99%
“…An obvious alternative is the use of bonding schemes that result in stronger, less labile surface bonds to provide a stable template for the junction. Examples include Si-C bonds resulting from alkene attachment to H-terminated silicon [84,145] and the use of aromatic diazonium reagents to result in SiÀC [66,67] and CÀC [10,72,121] bonds after electrochemical reduction of the diazonium ion. SiÀC and CÀC bond strengths are $4 eV, compared to $1.6 eV for AuÀS, making lateral motion of the molecules on the Si or C surface impossible at temperatures commonly experienced in top contact deposition.…”
Section: Progress Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…A simplified memristor device physics model [1] matched the experimental behavior [2] of nanocrossbar Pt/TiO 2 /Pt devices. Resistive switching in metal oxides has in fact seen more than four decades of scientific research [4][5][6][7][8][9][10][11][12][13][14][15], motivated in large part by that prospect of a fast and high density NVRAM technology [16][17][18][19][20][21][22][23]. The continuous resistance change exhibited by oxide switches also appears to meet analog switch requirements for neuromorphic computing [24][25][26].…”
Section: Introductionmentioning
confidence: 99%